2019
DOI: 10.1186/s12957-019-1563-2
|View full text |Cite
|
Sign up to set email alerts
|

Routine preoperative mechanical bowel preparation with additive oral antibiotics is associated with a reduced risk of anastomotic leakage in patients undergoing elective oncologic resection for colorectal cancer

Abstract: BackgroundAnastomotic leakage (AL) following colorectal resection is a serious issue. AL in oncologic patients might negatively affect the overall survival. Recently, mechanical bowel preparation with additive oral antibiotics (MBP + AB) prior to surgery has been suggested as a means of reducing AL. However, it is unclear whether this positive effect is secondary to MBP alone or secondary to the additive oral antibiotic (MBP + AB). The aim of this study was to investigate the effect of mechanical bowel prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The effectiveness of MBP with additive OA was confirmed. In conclusion, they recommended mechanical bowel preparation with additive non-absorbable oral antibiotics in preoperative period for elective colorectal surgery [33]. .035; open multivariable adjusted OR=0.3 (0.12-0.77), P=0.012).…”
Section: Mechanical Bowel Preparation (Mbp) and Preventive Oral Antib...mentioning
confidence: 94%
See 2 more Smart Citations
“…The effectiveness of MBP with additive OA was confirmed. In conclusion, they recommended mechanical bowel preparation with additive non-absorbable oral antibiotics in preoperative period for elective colorectal surgery [33]. .035; open multivariable adjusted OR=0.3 (0.12-0.77), P=0.012).…”
Section: Mechanical Bowel Preparation (Mbp) and Preventive Oral Antib...mentioning
confidence: 94%
“…MBP is performed before colorectal surgery to reduce massive bowel contents, which can be a source of colorectal AL and bacterial pathogens. Many studies have supported combined MBP and OA prior to planned colorectal surgery [32,33].…”
Section: Mechanical Bowel Preparation (Mbp) and Preventive Oral Antib...mentioning
confidence: 99%
See 1 more Smart Citation
“…The oral antibiotics were reintroduced in the context of MOAB, with studies demonstrating a postoperative reduction of AL following colectomy to almost 50% [42]. A more recent clinical trial further confirmed that the usage of MOAB significantly decreases AL rates in patients after CRC surgery [9]. Opioids used in perioperative analgesia, such as morphine, have been demonstrated to promote the adherence of collagenolytic E. faecalis to the anastomotic site, leading to AL in rats [98].…”
Section: The Role Of Intestinal Microbiota In Anastomotic Leakage After Crc Surgerymentioning
confidence: 99%
“…The concept of MBP has long been a standard practice in colorectal surgery, as it offers numerous advantages such as allowing a more feasible colonic manipulation and facilitating the detection of small colorectal tumors via palpation [ 9 ]. However, many studies that focus on the clinical value of MBP have reported that MBP does not prevent any postoperative surgical complications related to infection, possibly aggravating these adverse effects [ 10 , 11 ].…”
Section: The Effect Of Preoperative Mechanical Bowel Preparation Omentioning
confidence: 99%